Antioxidants effects in health the bright and the dark side - Nabavi, Seyed Mohammad; Silva, Ana Sanches (Elsevier, 2022)
"Antioxidants Effects in Health: The Bright and the Dark Side examines the role that antioxidants play in a variety of health and disease situations. The book discusses antioxidants’ historical evolution, their oxidative stress, and contains a detailed approach of 1) endogenous antioxidants, including endogenous sources, mechanisms of action, beneficial and detrimental effects on health, in vitro evidence, animal studies and clinical studies; 2) synthetic antioxidants, including sources, chemistry, bioavailability, legal status, mechanisms of action, beneficial and detrimental effects on health, in vitro evidence, animal studies and clinical studies; and 3) natural antioxidants, including sources, chemistry, bioavailability, mechanisms of action, possible prooxidant activity; beneficial and detrimental effects on health, in vitro evidence, animal studies and clinical studies. Throughout the boo, the relationship of antioxidants with different beneficial and detrimental effects are examined, and the current controversies and future perspectives are addressed and explored. Antioxidants Effects in Health: The Bright and the Dark Side evaluates the current scientific evidence on antioxidant topics, focusing on endogenous antioxidants, naturally occurring antioxidants and synthetic antioxidants. It will be a helpful resource for pharmaceutical scientists, health professionals, those studying natural chemistry, phytochemistry, pharmacognosy, natural product synthesis, and experts in formulation of herbal and natural pharmaceuticals."